2019
DOI: 10.5937/gp23-22853
|View full text |Cite
|
Sign up to set email alerts
|

Heat-waves and mortality in Czech cities: A case study for the summers of 2015 and 2016

Abstract: The aim of this paper was to assess the impact of heatwaves on mortality in ten Czech cities, using data recorded during the summers of 2015 and 2016. Temperature-related mortality during heatwaves was investigated by comparing mortality figures on heatwave days and those on other days by means of the Mann-Whitney U test. Results for all-cause mortality, cardiovascular and respiratory diseases (CVD+R) mortality, as well as for mortality in the over-65 age group, show statistically significant differences (p <0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…High air temperature (AT) in urban areas and especially their long-term occurrence in so-called heat waves cause intensive physical stress with negative impacts on human health. It was found that summer mortality in big cities was strongly associated with hot weather and heat wave duration and severity as reported by [6] for Shanghai, [7] for Chicago, [8] for Lisbon, [9] for Paris, [10] for Montreal and [11] from a city located in temperate climate. However, though the severity of heat waves did not increase generally during the 20th century, their incidence is predicted to alter dramatically, especially in the second half of the 21st century [12].…”
Section: Introductionmentioning
confidence: 84%
“…High air temperature (AT) in urban areas and especially their long-term occurrence in so-called heat waves cause intensive physical stress with negative impacts on human health. It was found that summer mortality in big cities was strongly associated with hot weather and heat wave duration and severity as reported by [6] for Shanghai, [7] for Chicago, [8] for Lisbon, [9] for Paris, [10] for Montreal and [11] from a city located in temperate climate. However, though the severity of heat waves did not increase generally during the 20th century, their incidence is predicted to alter dramatically, especially in the second half of the 21st century [12].…”
Section: Introductionmentioning
confidence: 84%
“…This study is based on the characterization of the climatic trends of human thermal comfort and its assessment during heat wave periods. From the standpoint of human health heat wave is a period of time in which an excessive stress of thermoregulation of the body is accessed, as well as an increased risk of morbidity and mortality, especially from respiratory and cardiovascular diseases (Robinson, 2001;Arsenović et al, 2019;Urban et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Mean-Decade Trends for Air Temperature and for PET in different parts ofRussian Federation in 1966-2015 …”
mentioning
confidence: 99%
“…Recently, heat waves (intervals of more than 5 consecutive days with a maximum temperature higher than 5°C in relation to average daily maximums), which are potentially dangerous for the population, especially for chronic patients and the elderly, are increasingly occurring. Arsenović et al (2019) found that during the summer of 2015 and 2016, the mortality rate in seven of the ten cities surveyed in the Czech Republic increased significantly. Ducic et al (2012) studied the types of atmospheric circulation as a possible cause of heavy rainfall in Crkvice in southwestern Montenegro, probably the rainiest place in Europe.…”
Section: Introductionmentioning
confidence: 98%